Machanical performance of encapsulated restorative glass ionomer cements for use with atraumatic restorative treatment (ART) - Cabral, Ricardo (2013)
Fil: Cabral, Ricardo. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Materiales Dentales; Argentina.